Evaluation analysis during discursive interactions in nursing courses through SDIS-GSEQ. - Ruiz-Carrillo, Edgardo; Bravo-Sánchez, Luisa; Meraz-Martínez, Samuel; Cruz-González, José Luis (Advances in Social Sciences Research Journal, 2016)
Background: Discourse in the field of education is structured in IRE/F patterns, which give the teacher the ability to lead interaction in the classroom. The objective of the study was to identify discourse patterns present in practical nursing courses, with a focus on the evaluation of the teacher and assistants. Method: The participants of the study were videotaped and the data obtained was recorded and categorized using the SDIS-GSEQ software in order to obtain discursive sequences. Results: The teacher and assistants used divergent IRE/F structures: the teacher gave an explanation after conducting an evaluation of the student in order to impart knowledge, and the assistants evaluated repeatedly and sought for evidence of knowledge in the students by asking them to give examples. Conclusion: The occupied roles will be defined as “guide/ primary expert” and “instigator/supervisor”, and these roles will persist even if the knowledge of the practice is or is not negotiated. It is recommended to take the discourse to conditions of greater negotiation of knowledge in order to improve teaching. [Keywords: mentors, patient simulation, discourse analysis, learning processes, teacher-student interaction]